PENGEMBANGAN MODUL FILSAFAT BAHASA - Suryanto, Sugeng; Hendriyanto, Agoes (Jurnal Pendidikan Bahasa dan Sastra, 2017)
This study aims to develop modules of course on the Language Philosophy in STKIP PGRI Pacitan. It held in the first year of 2013/2014 and the second year of 2015/2016. There are 3 phases of the development: problem identification, potential problems, and design of language philosophy modules. The result of the development in the first year are a module design of scientific language philosophy based on character values of Â Vol 1 and 2" ISBN 978-979-1533-19-5 and 978-979-1533-18-8. The second year study consisted of: student and expert validation, module revision, limited trial, module revision, extensive testing, module revision, print-ready module. Expert validation result was 89%, student debriefing questionnaire was 88,6%, mean score 88,8%. The result of the next phase of limited trial based on counts table (t12 = 2.77, t13 = 7.89, t14 = 8.96, t23 = 2.88, t24 = 4.69, t34 = 2.79) is bigger thant-table with 2,021 probabilities. After a limited test, we conclude that the scientific-language philosophy module based on the value of local wisdom is very feasible to use. Test process is broadly obtained that t-count table is bigger (t56 = 2.77, t57 = 6,48, and t67 = 2,29) than t-table 2,021. The scientific-language philosophy module based on the value of local wisdom "is worth to use, volumes 1 ISBN 978-602-25829-3-3 and volume 2 ISBN 978-602-25829-3-4.Keywords: module, philosophy, language, local wisdom